Modelling of gallium nitride half-bridge converter - Yeo, Howe Li (2018)
Gallium nitride high electron mobility transistors (GaN HEMTs) have been commonly cited to significantly improve the efficiency and power density of power electronic converters like battery chargers, laptop adapters and motor drives. The potential for size reduction was proven during the Google little box challenge where GaN HEMTs were used for the construction of the winner’s converter. The size of the magnetics components are significantly reduced due to the high switching frequencies. This has enabled the use of more advanced hardware design techniques like integration of magnetics and packaging. However, as they are relatively new to the field of power electronics, their characteristics are not well understood by many power electronics engineers. Hence, many developed simulation models for GaN HEMTs do not accurately reflect the device behaviour when they are used in power electronic applications. In present thesis work, the majority of models for GaN HEMTs are proposed for radio frequency applications. Relatively few models have been proposed for power electronic applications and the few that have been proposed use simplistic equations that do not accurately capture the device’s behaviour. In this thesis, the unique device physics associated with the GaN HEMT is reviewed and compared with that of other devices like the silicon MOSFET. Unlike other power transistors, the i-v characteristic of GaN HEMTs is significantly augmented by the piezoelectric effect. Also, unlike the body diode of silicon MOSFETs, the body diode of GaN HEMTs is affected by the applied gate bias. Hence, in this work, a device model is proposed with an i-v characteristic that is approximated using the equation of a charge sheet in a GaN HEMT under the effect of piezoelectric polarisation. An i-v characteristic equation for the body diode that reflects the effect of different gate biases is also proposed for the model. In order to capture the dynamic behaviour of the device, the capacitances have been modelled behaviourally using sigmoid functions. It is also well-known that parasitic inductances in a power electronic circuit hinder the performance of fast-switching devices. Many authors propose ways of minimising the parasitic inductances without regards to the implications this would have on other aspects of converter design such as the thermal resistance of the thermal path from the device’s junction to the ambient air. Hence, the implications of the trade-off in between a low parasitic inductance design and a low thermal-resistance is examined with respect to the volume and efficiency of a buck converter. This is done by examining the performance of GaN converters with different printed circuit board (PCB) layouts. As GaN switches are known to switch very quickly, it is very difficult to accurately observe their switching behaviour under practical conditions due to limitations in the bandwidth of current equipment. Consequently, this makes deducing the actual switching loss of a GaN switch difficult. Hence, in order to determine what method is useful for extracting the switching loss of GaN HEMTs, a review of loss measurement methods is conducted and two commonly used electrical methods are compared against each other in terms of accuracy. Lastly, two boost converters, one developed using silicon MOSFETs and the other developed using GaN HEMTs, are both constructed and tested for use as a bidirectional battery charger in a home energy storage system. The two are compared against each other in terms of volume, cost and efficiency to assess the benefit of GaN HEMTs. In the concluding chapter, findings are summarised and potential future work is proposed.